Characterization of structural motifs for interactions between glycosaminoglycans and proteins. (27th November 2017) - Yang, Jiyuan; Chi, Lianli
Abstract: Glycosaminoglycans (GAGs) are a family of linear and anionic polysaccharides that play essential roles in many biological and physiological processes. Interactions between GAGs and proteins regulate function in many proteins and are related to many human diseases and disorders. The structural motifs and mechanisms for interactions between GAGs and proteins are not fully understood. Specific bindings, including minor but unique sequences sporadically distributed along the GAG chains or variably sulfated domains interspersed by undersulfated regions, may be specifically recognized by defined domains of a variety of proteins. Understanding the molecular basis of these interactions will provide a template for developing novel glycotherapeutic agents. The present article reviews recent methodologies and progress on the characterization of structural motifs in both GAGs and proteins involved in GAG-protein interactions. The analytical approaches are categorized into three groups: affinity-based methods; molecular docking, nuclear magnetic resonance (NMR) spectroscopy and X-ray crystallography; and mass spectrometry (MS) techniques. The advantages and limitations of each category of methods are discussed and are based on examples of using these techniques to investigate binding between GAGs and proteins. Graphical abstract: Highlights: Methodologies for characterizing GAG-protein complexes are reviewed. Affinity measurement methods and spectroscopic approaches are described. Advantages and limitations of each method are discussed.